A new companion to digital humanities - Schreibman, Susan; Siemens, Raymond George; Unsworth, John (Blackwell Companions to Literature and Culture, 2016)
This highly-anticipated volume has been extensively revised to reflect changes in technology, digital humanities methods and practices, and institutional culture surrounding the valuation and publication of digital scholarship. A fully revised edition of a celebrated reference work, offering the most comprehensive and up-to-date collection of research currently available in this rapidly evolving discipline Includes new articles addressing topical and provocative issues and ideas such as retro computing, desktop fabrication, gender dynamics, and globalization Brings together a global team of authors who are pioneers of innovative research in the digital humanities Accessibly structured into five sections exploring infrastructures, creation, analysis, dissemination, and the future of digital humanities Surveys the past, present, and future of the field, offering essential research for anyone interested in better understanding the theory, methods, and application of the digital humanities